Internet Banking In India : The Study Of Impact Of Regulatory Framework On Customers Attitude Towards The Adoption Of Internet Banking - Atluri, Padma (2004)
Internet banking for retail segment is a recent development that has generated a lot of interest among the banks in India. This study was undertaken to examine the impact of regulatory framework, on the customers' attitude towards the adoption of Internet banking in India.